Borosilicate glass layers on Mycenaean glass: Surface alterations by glass–borax–gold interactions - Drünert, F.; Lind, F.; Vontobel, P.; Kamitsos, E. I.; Wondraczek, Lothar; Möncke, D. (Journal of Non-Crystalline Solids: X, 2019)
A previous report (Möncke et al., PCG 2013) discussed the possible formation of a borosilicate layer on the surface of Late Bronze Age glass samples (Mycenaean period, excavated in Palaia Epidavros, Greece). Now, we investigate potential mechanisms for such suggested borate incorporation into the surface of alkali-lime silicate glasses. Since former studies reported that glass relief fragments have been found alongside gold foils featuring identical reliefs, we tested the hypothesis that borates could have been introduced through gold working via the reaction of a borax-treated gold foil with the silicate glass surface at elevated temperature. A borosilicate layer was successfully generated on replica soda lime silicate glass samples and identified by vibrational spectroscopy. Different approaches were used in order to merge gold sheets to the glass samples. At temperatures above 800 °C, borax could have been used either as a solder in the fusion process between a gold sheet and the glass surface, or borate was transferred from the gold sheet previously in contact with a borax melt, presumably for cleaning gold or during ore extraction. The depth of the borosilicate layer on the thus treated glasses extents from the surface several μm into the bulk glass as probed by micro-Raman and IR spectroscopy, while the dimensions of the spread across the glass surface can be visualized by neutron radiography.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Borax; Borosilicate layer; FT-IR spectroscopy; Gold processing; Mycenaean glass; Neutron radiography; Raman spectroscopy